If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 6y = 36 Solving 9x + 6y = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 9x + 6y + -6y = 36 + -6y Combine like terms: 6y + -6y = 0 9x + 0 = 36 + -6y 9x = 36 + -6y Divide each side by '9'. x = 4 + -0.6666666667y Simplifying x = 4 + -0.6666666667y
| 1.75(2x+5)=6 | | 3x-4(x+1)=-(7x+4)+x | | -5(6m-2)=10 | | 0.4n+0.1=0.5(n+4) | | 4y+16=24x-2y | | 6x^2-12x-5=0 | | 8x-9=1211x | | 2x=-3x+15 | | 49(2x-12)=38(3x+9) | | 12+-8z=-12 | | -10.6=x | | 8x-0=12+11x | | 14x+12=7x+35 | | 6.8(x-4)=-0.2x+21.8 | | 8x+4y=32 | | 5(a+6)=6+a | | 4(x-3)=-4x+52 | | x+0.77=9.3 | | -9m-[2(11-2m)+14]=7m | | 7x-1=139 | | 10=-2c+22 | | 12x-5=5x+16 | | 8x+y=21 | | 8p+p=11-3p | | 8x+x=21 | | (x+4)2=7 | | -6x-13x=95 | | 5(1+4m)-2m=13 | | 4x^2+11x+20=0 | | 8-5x+x=24 | | 3x^2-30=13x | | .4s=-16 |